Increased activities of both superoxide dismutase and catalase were indicators of acute depressive episodes in patients with major depressive disorder - Tsai, Meng-Chang; Huang, Tiao-Lai (Psychiatry research, 2016)
Oxidative stress may play an important role in the pathophysiology of major depressive disorder (MDD). The aim of this study was to investigate the serum levels of oxidative stress biomarkers and S100B in patients with MDD in an acute phase, and evaluate the changes in superoxide dismutase (SOD), protein carbonyl content (PCC), glutathione peroxidase (GPX), 8-hydroxy 2'-deoxyguanosine after treatment (8-OHdG), catalase (CAT), thiobarbituric acid reactive substances (TBARS) and S100B. We consecutively enrolled 21 MDD inpatients in an acute phase and 40 healthy subjects. Serum oxidative stress markers were measured with assay kits. Serum SOD and CAT activities in MDD patients in an acute phase were significantly higher than those of healthy subjects, and serum PCC levels were significantly lower. The HAM-D scores had a significantly positive association with S100B levels. Eighteen depressed patients were followed up, and there was no significant difference among all of the markers after treatment. In conclusion, our results suggest that increased activities of both SOD and CAT might be indicators of acute depressive episodes in MDD patients. •We found that increased activities of both SOD and CAT might be indicators of acute depressive episodes in MDD patients.•We found S100B might be a biomarker of severity of depression in MDD.